KEPEMIMPINAN KEPALA SEKOLAH DALAM MEMBANGUN SEKOLAH BERKUALITAS DI SEKOLAH DASAR - Minsih, Minsih; Rusnilawati, Rusnilawati; Mujahid, Imam (Universitas Muhammadiyah Surakarta, 2019)
Principal leadership was a determining factor in the education process in MI Muhammadiyah Special Program Kartasura. Principal leadership emphasized the formation of student character and not on student grades. The purpose of this study was to describe the leadership style applied and the role of principals as leaders in building high-quality school. This type of research was qualitative research. The research design used was phenomenology. Research used primary data in the form of interviews and observations and used secondary data in the form of documents obtained from school. The data analysis used was an interactive model analysis with source triangulation and methods. The results of this study were: First. Principal leadership had a democratic-monarchic leadership style. This was based on the system that applied in the process of determining policies and decision-making processes carried out jointly. Second, the role of the principal included several aspects that had been carried out, namely: as an educator, as a manager, as an administrator, as a supervisor, as a leader, as an innovator, as a very good motivator. The principal could be an example in carrying out their duties. Therefore, the type and character of the leader must be observed and assessed properly.